Pesticides And Soil Pollution: Health Risks That Threaten To Human Life - Mulia, Mimin Indriani (Universitas Nahdlatul Ulama Surabaya, 2024)
Soil as a natural resource that acts as a medium for plant growth, soil provides nutrients, water, and physical support for plants. In addition, soil also functions as a carbon store, helping to regulate the climate by absorbing greenhouse gases. The process of soil formation involves complex interactions between minerals, organic matter, water, and living organisms. Soil pollution is increasingly having serious impacts on human health and ecosystems. Waste from human activities and the use of pesticides are the biggest causes of soil pollution. Some efforts that can be made to prevent soil pollution are bioremediation, monitoring pesticide use, phytoremediation techniques, and education. The use of pesticides in agriculture does have a significant impact on human health, both in the short and long term. Therefore, it is very important to implement effective control measures to reduce pesticide contamination and protect public health.